Numerical simulation of gas production from permafrost hydrate deposits enhanced with CO2/N2 injection. (15th April 2021) - Kan, Jing-Yu; Sun, Yi-Fei; Dong, Bao-Can; Yuan, Qing; Liu, Bei; Sun, Chang-Yu; Chen, Guang-Jin
Abstract: A new numerical simulator was developed from the widely used CH4 hydrate simulator TOUGH + HYDRATE to realize the simulation of hydrate exploitation by CO2 /N2 –CH4 replacement. Focusing on actual hydrate reservoir, CO2 /N2 injection combined with depressurization in a practical continuous injection-production mode was applied for gas production. The influence of feed gas composition and injection pressure on CO2 sequestration and CH4 production was investigated. Moreover, we conducted a fair comparison and revealed the advantages of CO2 /N2 injection over two traditional methods in gas/water production performance. During gas injection, a continuous CO2 /N2 separation process under stratum environment was observed, and the whole gas replacement process can be roughly summarized as a continuous cycle of CH4 hydrate dissociation and CO2 /N2 hydrate formation. Increasing N2 mole fraction from 30% to 50% significantly enhanced the CH4 production efficiency, while its increase from 50% to 100% mainly resulted in more N2 production and higher injection-production ratio. Raising the injection pressure from 4.5 to 5 MPa improved CH4 recovery by 1.5 times, while increase from 5 to 7 MPa reduced CH4 recovery by 8.3%. A favorable CH4 recovery with relatively low cost can be achieved by finding an appropriate balance between CH4 release and CO2 sequestration. Highlights: A new numerical simulator for hydrate exploitation by gas exchange is developed. Field-scale hydrate exploitation enhanced with CO2 /N2 injection is simulated. Balancing CH4 release against CO2 storage benefits CH4 recovery and energy saving. Gas production performance can be improved according to the controlling factors.